On and Off-Body Radio Channel Performance of a Dual Band and Dual Mode Antenna - Mohammad Monirujjaman Khan, (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, measurement results of onbody radio propagation channels at 2.45 GHz and offbody radio propagation channels at 1.9 GHz using dual band and dual mode (DBDM) antenna are presented. The proposed antenna works at two different frequencies with different radiation modes. Experiments are performed first in the chamber and then in an indoor environment. The path loss has been characterized for ten different on-body radio channels at 2.45 GHz. Five off-body radio channels are studied at 1.9 GHz. The path loss was modeled as a function of distance for onbody radio propagation at 2.45 GHz and off-body radio propagation at 1.9 GHz. For on-body propagation, the path loss exponent is noticed to be 2.48 and 2.22 in the camber and sensor laboratory, respectively. For offbody radio propagation case, the path loss exponent is noticed to be 1.27. The proposed antenna shows very good on-body and off-body radio propagation channel performance.